Investigating the effect of roasting on functional properties of defatted hazelnut flour by response surface methodology (RSM). Issue 1 (September 2015) - Turan, Deniz; Capanoglu, Esra; Altay, Filiz
Abstract The effect of roasting on functional properties of defatted hazelnut flours was evaluated by using response surface methodology (RSM). Color, water absorption capacity, emulsion and foaming properties were the main responses that determine the degree of roasting. After roasting of hazelnuts, the oil absorption and water absorption capacity, foam and emulsion stability of the flour were increased, whereas bulk density, foaming capacity and emulsion activity of flours decreased. The roasting temperature was found to be the main factor affecting color development, emulsion properties and foaming capacity. The maximum responses for color, emulsion and foaming properties were obtained at 140 °C and 40 min from the regression equations. RSM is a useful tool which can be applied to adjust the desired functional properties of flours. The results indicated that roasted defatted hazelnut flours may have a good potential to be used as value-added food ingredients, similar to other protein sources with various functional properties for food applications due to their nutritional value and improved functionality.